The innovative entrepreneur - Spulber, Daniel F. (Cambridge : Cambridge University Press, 2014)
Innovative entrepreneurs are the prime movers of the economy. The innovative entrepreneur helps to overcome two types of institutional friction. First, existing firms may not innovate efficiently due to incumbent inertia resulting from adjustment costs, diversification costs, the replacement effect, and imperfect adjustment of expectations. The innovative entrepreneur compensates for incumbent inertia by embodying innovations in new firms that compete with incumbents. Second, markets for inventions may not operate efficiently due to transaction costs, imperfect intellectual property protections, costs of transferring tacit knowledge, and imperfect information about discoveries. The innovative entrepreneur addresses inefficiencies in markets for inventions through own-use of discoveries and adoption of innovative ideas. The Innovative Entrepreneur presents an economic framework that addresses the motivation of the innovative entrepreneur, the innovative advantage of entrepreneurs versus incumbent firms, the effects of competitive pressures on incentives to innovate, the consequences of creative destruction, and the contributions of the innovative entrepreneur to the wealth of nations.
Machine generated contents note: 1. Introduction; 2. Entrepreneurial motivation: maximizing life-cycle utility; 3. Innovative advantage: entrepreneurial initiative and incumbent inertia; 4. Competitive pressures and entrepreneurial incentives to innovate; 5. Creative destruction: transaction costs and intellectual property rights; 6. Creative destruction: making new combinations; 7. Creative destruction: tacit knowledge; 8. Creative destruction: asymmetric information; 9. The wealth of nations: international trade and investment; 10. Conclusion.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Entrepreneurship; Creative ability in business